Aphid Behavior on Amaranthus hybridus L. (Amaranthaceae) Associated with Ocimum spp. (Lamiaceae) as Repellent Plants - Yarou, Boni Barthélémy; Bokonon-Ganta, Aimé H.; Verheggen, François J.; Lognay, Georges C.; Frédéric, Francis (My University, 2020)
Various plant species contain biocidal and/or semiochemical components. These can be used for managing insect pests, in order to reduce the use of synthetic pesticides and to improve the quality of vegetable crops. This study was conducted to assess the effect of repellent plants Ocimum gratissimum L. and Ocimum basilicum L. on aphids Aphis craccivora Koch, Aphis fabae Scopoli and Myzus persicae Sulzer when they are associated with Amaranthus hybridus L. plants. The results have shown that in the two approaches tested—Ocimum sp. plants surrounded by A. hybridus plants and the dual-choice test—the number of aphids on the A. hybridus plant associated with either O. gratissimum or O. basilicum was significantly less significant compared to the A. hybridus alone. This first study on the association between A. hybridus and Ocimum spp. shows that the Ocimum species might be used as an alternative method for controlling aphids in order to avoid the use of synthetic pesticides on Amaranthus. The ability of Ocimum spp. to repel pests can make it an important companion plant for farmers, because those plants can not only be used to control pests, but they can also be harvested, providing a direct economic return.
Keywords: aphids; basil; pest control; amaranth; repellent activity; companion plant